2013
DOI: 10.1371/journal.pone.0077464
|View full text |Cite
|
Sign up to set email alerts
|

Human Neonatal Cardiovascular Progenitors: Unlocking the Secret to Regenerative Ability

Abstract: Although clinical benefit can be achieved after cardiac transplantation of adult c-kit+ or cardiosphere-derived cells for myocardial repair, these stem cells lack the regenerative capacity unique to neonatal cardiovascular stem cells. Unraveling the molecular basis for this age-related discrepancy in function could potentially transform cardiovascular stem cell transplantation. In this report, clonal populations of human neonatal and adult cardiovascular progenitor cells were isolated and characterized, reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…miRNA are well described post-transcriptional regulators of gene expression, participating in many pathophysiological mechanisms in the cardiovascular system56, as well as in progenitors biology and cardiomyocyte proliferation5758. Additionally, miRNA expression can be affected by β-blockers treatment, and miRNAs can be directly involved in the β-adrenergic transduction cascade578.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA are well described post-transcriptional regulators of gene expression, participating in many pathophysiological mechanisms in the cardiovascular system56, as well as in progenitors biology and cardiomyocyte proliferation5758. Additionally, miRNA expression can be affected by β-blockers treatment, and miRNAs can be directly involved in the β-adrenergic transduction cascade578.…”
Section: Discussionmentioning
confidence: 99%
“…With age, the regenerative capacity of cardiovascular progenitors found within the heart decreases [ 12 ]. We have previously reported that Isl-1 positive cardiovascular progenitors isolated from the neonatal and adult heart exhibit age—dependent disparities in functional parameters such as cell cycle progression and invasion which may stem from underlying differences in gene and microRNA expression [ 13 ]. Determining the effect of simulated microgravity on resident cardiac progenitor cell function in vitro , and whether this effect is dependent on age would have implications not only for space flight, but would also provide evidence as to whether alterations in gravitational force could be utilized as a therapeutic for improved cardiovascular stem cell function.…”
Section: Introductionmentioning
confidence: 99%
“…Murine or human Isl1 + cells derived from embryonic stem cells have been shown to give rise to cardiomyocytes, which exhibit appropriate electrophysiological properties, such as action potentials and Ca 2+ transients (Cagavi et al, 2014 ), as well as smooth muscle cells and endothelial cells (Lui et al, 2013 ). Contrary to previous assumptions, Isl1 + cells are not exclusively in an embryonic state because there is a subpopulation of endogenous CSCs that persist throughout life and co-express both c-kit and isl1 (Fuentes et al, 2013 ). Because all progenitor cells expressing Isl1 also express c-kit but not all c-kit + cells express Isl1, Isl1 + c-kit + progenitor cells may be a subpopulation of c-kit + progenitors (Fuentes et al, 2013 ).…”
Section: Isl1 + Stem Cellsmentioning
confidence: 78%
“…Contrary to previous assumptions, Isl1 + cells are not exclusively in an embryonic state because there is a subpopulation of endogenous CSCs that persist throughout life and co-express both c-kit and isl1 (Fuentes et al, 2013 ). Because all progenitor cells expressing Isl1 also express c-kit but not all c-kit + cells express Isl1, Isl1 + c-kit + progenitor cells may be a subpopulation of c-kit + progenitors (Fuentes et al, 2013 ).…”
Section: Isl1 + Stem Cellsmentioning
confidence: 78%
See 1 more Smart Citation